Exercise During the Childbearing Year - Hammer, Roger L. (2000)
Many women wish to continue to pursue an active lifestyle during pregnancy, while the pregnancy itself may provide the motivation for other more sedentary women to begin an exercise program for the sake of improved health/fitness. Also, female competitive athletes, upon becoming pregnant, may wish to continue sports performance and require careful monitoring to assure maternal-fetal safety. This review is designed to assist the perinatal educator who is in the position to advise the pregnant patient on the risks and benefits of physical activity during the childbearing year and provide suggestions for developing individualized exercise programs.